Lithium ion secondary battery
By using multi-layer coating technology and a combination of different active materials in the negative electrode sheet of lithium-ion batteries, combined with the characteristics of silicon oxygen materials and silicon carbon materials, the polarization and dynamic performance problems caused by volume expansion during charging and discharging of lithium-ion batteries are solved, and higher fast charging and safety performance are achieved.
Patent Information
- Application Number
- CN202411954279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-18
AI Technical Summary
During the charging and discharging process, existing lithium-ion batteries have increased polarization and decreased kinetic performance due to volume expansion of silicon negative electrode material, and insufficient fast charging and safety performance.
The negative electrode sheet multi-layer coating technology is used to utilize specific active materials in different coatings, combining the advantages of silicon oxygen materials and silicon carbon materials, and controlling the size of the battery cell and shell to reduce the impact of volume expansion on safety.
Significantly reduce polarization, improve the battery's dynamic performance and fast charging performance, while improving the battery's safety performance and cycle stability.
Smart Images

Figure CN119852489A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art
[0002] As an important component of sustainable energy, battery technology has greatly promoted the sustainable development of society and the convenience and intelligence of human life. Among them, lithium-ion batteries have the advantages of high energy density and long cycle life, and have been widely used in mobile phones, laptops, power tools, new energy vehicles and energy storage. According to market research, mileage anxiety, charging problems, and safety issues greatly affect the user experience of new energy vehicles, which shows that power batteries are in urgent need of targeted technological innovation. Therefore, power batteries that take into account both safety performance and fast charging performance have become a key research direction.
[0003] Silicon negative electrode material has an ultra-high theoretical specific capacity (4200mAh / g), and has become an important negative electrode material for improving the energy density of lithium batteries. However, due to its special alloying lithium insertion mechanism, its volume expands greatly during the charging process (up to about 300%). Its high volume expansion makes it easy to increase the polarization of the negative electrode and reduce the kinetic performance during the charging and discharging process; and the repeated expansion and contraction of silicon particles will also cause the particles to break and pulverize, resulting in material failure; it is also not conducive to maintaining the integrity of the SEI film, resulting in continuous side reactions at the negative electrode interface that consume electrolyte, which will affect the cycle life of the battery. Summary of the invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium ion secondary battery. The lithium ion secondary battery (hereinafter referred to as battery) of the present invention can take into account both fast charging capability and high safety.
[0005] The inventors of the present invention have found that the negative electrode sheet is a single-layer coating structure, and the components of this structure are uniform and consistent, which has the advantage of good consistency. However, it is precisely because of the good consistency of this structure that the wetting effect of the electrolyte from the bottom layer to the surface layer of the electrode sheet and the distribution of the current density are uneven, causing polarization inside the electrode sheet, and the surface polarization is larger and the bottom polarization is smaller. This uneven polarization will be more obvious when the charging and discharging current increases, causing the surface active material in the electrode sheet to preferentially deintercalate lithium, and the bottom active material to deintercalate lithium more lagging. For the negative electrode, excessive polarization will affect the kinetic performance of the negative electrode, causing lithium precipitation when the charging rate increases, thereby affecting the safety performance and fast charging performance of the battery. Therefore, the inventors of the present invention adopt a multi-layer coating technology for negative electrode sheets (for example, a double-layer coating technology), and according to the polarization laws of the surface and bottom layers in the negative electrode sheets, use different and specific active materials in different coatings to solve the problem of excessive polarization of the negative electrode, thereby improving the fast charging performance of the battery, and at the same time, by controlling the size of the battery cell and the outer casing, reduce the impact of the volume expansion of the silicon negative electrode material on the battery safety, thereby improving the safety performance of the battery.
[0006] Taking into account the adverse effects of the volume expansion of silicon negative electrode materials on the battery and the polarization law of the surface and bottom layers of the negative electrode sheet, the inventors of the present invention have found that silicon-oxygen materials can be arranged on the surface of the negative electrode sheet away from the current collector, and silicon-carbon materials can be arranged on the surface of the negative electrode sheet close to the current collector, and by controlling the relationship between the size of the accommodation space formed by the shell in the thickness direction and the thickness of the battery cell, it is possible to take into account both fast charging capability and high safety. The reason is:
[0007] First, the silicon oxide material is a silicon oxide negative electrode material (SiO x , 0<x<2), lithium ions have a higher diffusion rate in silicon-oxygen materials, so silicon-oxygen materials have better kinetic properties, but because silicon-oxygen materials themselves lack constraints on the volume expansion of silicon, their volume expansion rate is larger than that of silicon-carbon materials.
[0008] Second, silicon-carbon materials are generally formed by depositing nano-silicon particles in a carbon skeleton, where the carbon skeleton can inhibit the volume expansion of silicon to a certain extent and provide a certain buffer space for the expansion of silicon particles. Therefore, the volume expansion of silicon-carbon materials is lower than that of silicon-oxygen materials. However, since the carbon skeleton of silicon-carbon materials is not conducive to the conduction of lithium ions, the kinetic properties of silicon-carbon materials are poor, and lithium precipitation is more likely to occur during fast charging.
[0009] In summary, taking into account the respective characteristics of silicon-carbon materials and silicon-oxygen materials, and combining the polarization laws of the surface and bottom layers of the negative electrode sheet, the silicon-oxygen material with excellent kinetic characteristics is placed on the surface layer of the negative electrode sheet, and the silicon-carbon material with slightly worse kinetic performance but higher structural stability is placed on the bottom layer of the negative electrode sheet. During fast charging, the silicon-oxygen material on the surface can exert its kinetic advantages to quickly insert lithium, and then conduct lithium ions to the bottom layer. The silicon-carbon material on the bottom layer has a stable structure and can maintain good adhesion with the negative electrode current collector. The above conditions can achieve complementary advantages, give full play to the kinetic advantages of silicon-oxygen materials and the structural stability advantages of silicon-carbon materials, and then improve the kinetic performance of the negative electrode sheet, thereby improving the fast charging performance of the battery. At the same time, by controlling the relationship between the size of the accommodating space formed by the outer shell in the thickness direction and the thickness of the battery cell, the battery cell can achieve a better fit with the outer shell in size, reducing the impact of the volume expansion of the silicon negative electrode material on the safety of the battery. Based on this, the inventors of the present invention proposed the following scheme:
[0010] The present invention provides a lithium-ion secondary battery, the lithium-ion secondary battery comprising a battery core and a shell, the battery core is located in a receiving space formed by the shell, and the battery core comprises a positive electrode sheet, a separator and a negative electrode sheet;
[0011] The positive electrode sheet includes a nickel-cobalt-manganese ternary material;
[0012] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; the first negative electrode active material layer comprises a silicon-oxygen material; the second negative electrode active material layer comprises a silicon-carbon material;
[0013] The thickness expansion coefficient K0 of the lithium ion secondary battery is 85%-93%;
[0014] The thickness expansion coefficient K0 = (T0 / T) × 100%,
[0015] Wherein, T is the dimension of the accommodation space in the thickness direction, in mm, and T0 is the thickness of the battery cell when the lithium-ion secondary battery is in a 0% SOC state, in mm.
[0016] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0017] (1) Compared with a single layer, the double-layer coated negative electrode of the present invention can significantly reduce polarization and improve the dynamic performance of the battery;
[0018] (2) The dimensions of the battery cell and the housing of the present invention are highly compatible in the thickness direction, which can improve the safety performance of the battery;
[0019] (3) The battery of the present invention can have both good fast charging performance and high cycle stability.
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Shown is a schematic structural diagram of the negative electrode sheet of the present invention.
[0022] Figure 2 Shown is a schematic structural diagram of a lithium-ion secondary battery of the present invention.
[0023] Figure 3 Shown is a schematic diagram of the thickness of the battery cell of the present invention.
[0024] Figure 4 Shown is a SEM image of the negative electrode sheet of the present invention. DETAILED DESCRIPTION
[0025] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0026] The present invention provides a lithium-ion secondary battery, the lithium-ion secondary battery comprising a battery core and a shell, the battery core is located in a receiving space formed by the shell, and the battery core comprises a positive electrode sheet, a separator and a negative electrode sheet;
[0027] The positive electrode sheet includes a nickel-cobalt-manganese ternary material;
[0028] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; the first negative electrode active material layer comprises a silicon-oxygen material; the second negative electrode active material layer comprises a silicon-carbon material;
[0029] The thickness expansion coefficient K0 of the lithium ion secondary battery is 85%-93%;
[0030] The thickness expansion coefficient K0 = (T0 / T) × 100%,
[0031] Wherein, T is the dimension of the accommodation space in the thickness direction, in mm, and T0 is the thickness of the battery cell when the lithium-ion secondary battery is in a 0% SOC state, in mm.
[0032] In the present invention, "the lithium ion secondary battery is in a 0% SOC state" means that the lithium ion secondary battery is discharged to a lower limit voltage [eg, 2.75 V for ternary high nickel materials (the molar content of elemental nickel is 80% and above)].
[0033] like Figure 1 and Figure 4 As shown, the negative electrode sheet includes a negative electrode collector 1 and a negative electrode active material layer 2 located on at least one side of the negative electrode collector 1; the negative electrode active material layer 2 includes a first negative electrode active material layer 21 and a second negative electrode active material layer 22 stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer 21 is away from the negative electrode collector, and the second negative electrode active material layer 22 is close to the negative electrode collector. The first negative electrode active material layer 21 includes a silicon-oxygen material 211, and the second negative electrode active material layer 22 includes a silicon-carbon material 221.
[0034] The thickness expansion coefficient K0 of the lithium ion secondary battery may be 85%-93% (e.g., 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92% or 93%). The thickness expansion coefficient K0=(T0 / T)×100%, where Figure 2 and Figure 3 As shown, T is the size of the accommodation space in the thickness direction, and T0 is the thickness of the battery cell when the lithium-ion secondary battery is in a 0% SOC state. When the battery cell is a wound type, the thickness of the battery cell is the diameter of the outermost arc of the arc area of the wound type battery cell, that is, the distance between the two tangents of the outermost arc of the arc area in the thickness direction; when the battery cell is a laminated type, the thickness of the battery cell is the vertical distance between the two outermost electrodes of the laminated type battery cell in the thickness direction.
[0035] The present invention arranges the first negative electrode active material layer including silicon oxygen material away from the negative electrode current collector (i.e., the first negative electrode active material layer including silicon oxygen material is located on the surface layer), so that the silicon oxygen material located on the surface layer can take advantage of the faster diffusion speed of electrons and lithium ions in the silicon oxygen material, preferentially deintercalate lithium during high rate charging, and transfer lithium ions to the bottom layer in time; arranges the second negative electrode active material layer including silicon carbon material close to the negative electrode current collector (i.e., the second negative electrode active material layer including silicon carbon material is located on the bottom layer), so that the silicon carbon material located on the bottom layer can take advantage of its lower expansion, provide more lithium intercalation sites during charging, and reduce the overall expansion of the negative electrode sheet, thereby reducing the polarization of the electrode sheet. At the same time, by controlling the thickness expansion coefficient K0 of the lithium ion secondary battery to meet the above range, the internal space utilization rate of the battery can be higher, which can not only avoid the collision between the battery cell and the shell to cause safety problems, but also reserve appropriate space for the expansion of the battery cell, and avoid the battery shell being squeezed due to excessive expansion, causing the battery to deform and deteriorate the battery performance, so that the battery can take into account both good fast charging performance and high safety performance.
[0036] When K0 is lower than 85%, the utilization rate of the accommodating space formed by the shell is low, the remaining space is large, the cycle stability of the battery is poor, and the energy density of the battery is relatively low; when K0 is higher than 93%, the remaining space of the accommodating space is small, and the energy density of the battery is relatively high, but the current and impedance increase accordingly, the heat generation of the battery is high, and the safety risk is greater.
[0037] In the present invention, by arranging silicon-oxygen material on the surface of the negative electrode sheet away from the current collector, arranging silicon-carbon material on the surface of the negative electrode sheet close to the current collector, and controlling the thickness expansion coefficient K0 of the lithium-ion secondary battery, compared with the prior art, the battery can have both good fast charging performance and high safety performance. In order to further improve the effect, one or more of the technical features can be further optimized.
[0038] In one example, K0 is 89%-92%.
[0039] In one example, the thickness expansion coefficient K of the lithium-ion secondary battery is 100 is 95%-99.9% (e.g., 95%, 96%, 97%, 98%, 99% or 99.9%), the thickness expansion coefficient K 100 =(T 100 / T)×100%,T 100 is the thickness of the battery cell when the lithium-ion secondary battery is in a 100% SOC state, in mm. Controlling the thickness expansion coefficient K of the lithium-ion secondary battery 100When within the above range, the expanded battery cell can maintain a good physical structure inside the battery. The battery will not be deformed and the battery performance will not deteriorate due to the compression of the outer shell due to excessive expansion, nor will the battery cell and the outer shell expand due to excessive air remaining inside the expanded battery, causing safety problems. At the same time, it is also conducive to the release of heat, avoiding the heat accumulation caused by the heat generated by the nickel-cobalt-manganese ternary material and silicon material (including silicon-oxygen material and silicon-carbon material) during the charging and discharging process, which may damage the ear and cause safety problems, thereby further improving the safety performance of the battery.
[0040] In the present invention, "the lithium ion secondary battery is in a 100% SOC state" means that the lithium ion secondary battery is charged to an upper limit voltage [eg 4.2 V for ternary high nickel materials (the molar content of elemental nickel is 80% and above)].
[0041] In one example, K 100 It is 97%-99%.
[0042] According to a specific embodiment, K0 is 89%-92%, K 100 It is 97%-99%.
[0043] In one example, the rebound rate R of the negative electrode sheet is 100 8%-45% (e.g., 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%), the rebound rate R 100 =[(H 100 -H) / H]×100%, H is the thickness of the negative electrode sheet, in μm, H 100 is the thickness of the negative electrode sheet when the lithium-ion secondary battery is in a 100% SOC state, in μm. Controlling the rebound rate R of the negative electrode sheet 100 In the above range, the expansion of the negative electrode sheet can be kept within a moderate range, which can not only ensure that the negative electrode active material layer maintains good contact with the negative electrode current collector (e.g., copper foil) during the charge and discharge process without peeling off, but also prevent the negative electrode active material layer from failing due to excessive expansion. 100 When it is lower than 8%, the gap of the negative electrode sheet is small, which affects the infiltration of the electrolyte into the negative electrode sheet and reduces the fast charging performance of the battery; when the rebound rate of the negative electrode sheet R 100 When it is higher than 45%, the expansion of the negative electrode sheet is too large, which may cause the battery and the shell to be squeezed to a large extent, causing the battery to deform. In addition, the remaining space in the shell is too small, which is not conducive to the diffusion of heat and the safety of the battery is poor.
[0044] Wherein, H is the thickness of the negative electrode sheet when the lithium ion secondary battery is discharged to 2.5 V. In the present invention, the thickness of the negative electrode sheet is the overall thickness of the negative electrode sheet, for example, when there is a negative electrode active material layer on one side of the negative electrode current collector, the thickness of the negative electrode sheet is the sum of the thickness of the negative electrode current collector and the thickness of the negative electrode active material layer on this side; when there are negative electrode active material layers on both sides of the negative electrode current collector, the thickness of the negative electrode sheet is the sum of the thickness of the negative electrode current collector and the thickness of the negative electrode active material layers on both sides.
[0045] In one example, R 100 It is 25%-40%.
[0046] In one example, the rebound rate R0 of the negative electrode sheet is 0.1%-7% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6% or 7%), and the rebound rate R0 = [(H0-H) / H]×100%, H is the thickness of the negative electrode sheet, in μm, and H0 is the thickness of the negative electrode sheet when the lithium-ion secondary battery is in a 0% SOC state, in μm. When the rebound rate R0 of the negative electrode sheet is controlled within the above range, the expansion of the negative electrode sheet is within a moderate range, which can not only keep the silicon-oxygen material and / or silicon-carbon material in good particle integrity, but also avoid particle breakage problems, causing the silicon-oxygen material and / or silicon-carbon material to fail, reducing the transmission rate of lithium ions, and causing the bonding network of the negative electrode sheet to fail, and particles fall to the positive electrode or the outer shell to cause safety problems, such as short circuits.
[0047] In one example, R0 is 0.5%-5%.
[0048] According to a specific embodiment, R 100 It is 25%-40%, and R0 is 0.5%-5%.
[0049] In one example, the silicon-oxygen material includes element Si and element O. In the silicon-oxygen material, the mass ratio of element Si to element O is m1; the silicon-carbon material includes element Si, element C, and element O. In the silicon-carbon material, the mass ratio of element Si to element O is m2; m1 < m2. By controlling the mass ratio of element Si to element O in the silicon-oxygen material in the first negative electrode active material layer < the mass ratio of element Si to element O in the silicon-carbon material in the second negative electrode active material layer, the oxygen element distribution on the surface layer of the negative electrode sheet is higher than that on the bottom layer, thereby improving the electron and lithium ion transmission rates on the surface layer, enabling the battery to have more excellent kinetic performance, and the higher electron and lithium ion transmission rates on the surface layer can make electrons and lithium ions transfer to the bottom layer more quickly, thereby making the overall current density distribution of the negative electrode sheet more uniform, avoiding the occurrence of internal polarization phenomena in the electrode sheet, and at the same time, enabling the silicon-carbon material on the bottom layer to maintain a high specific capacity, thereby improving the overall energy density of the battery, enabling the battery to balance better fast charging performance and cycle stability, and having a low cycle expansion rate.
[0050] In one example, m1 / m2 is 0.001 - 0.12 (for example, 0.001, 0.005, 0.01, 0.05, 0.1, 0.11, or 0.12).
[0051] In one example, m1 / m2 is 0.0023 - 0.05.
[0052] In one example, m1 is 0.8 - 1.2 (for example, 0.8, 0.9, 1, 1.1, or 1.2). By controlling the mass ratio of element Si to element O in the silicon-oxygen material in the surface layer within the above range, the optimized Si / O ratio can promote the transmission of ions and electrons in the silicon-oxygen material, and at the same time inhibit the particle expansion of the silicon-oxygen material during charge and discharge.
[0053] In one example, m1 is 0.9 - 1.
[0054] In one example, m2 is 7.5 - 500 (for example, 7.5, 10, 50, 100, 150, 200, 250, 300, 350, 400, 450, or 500). By controlling the mass ratio of element Si to element O in the silicon-carbon material in the bottom layer within the above range, the silicon-carbon material can have a high specific capacity, which is beneficial to improving the energy density of the battery.
[0055] In one example, m2 is 20 - 400.
[0056] According to a specific embodiment, m1 / m2 is 0.0023 - 0.05, m1 is 0.9 - 1, and m2 is 20 - 400.
[0057] In one example, in the silicon-carbon material, the mass ratio of element Si to element C is 0.6-1.5 (for example, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4 or 1.5). In the present invention, the mass ratio of element Si to element C can be obtained by EDS testing. For example, 5 silicon-carbon materials are randomly selected in the second negative electrode active material layer, and the mass ratio of element Si to element C is tested. The average value of the mass ratio of element Si to element C in the 5 silicon-carbon materials is calculated as the mass ratio of element Si to element C.
[0058] By controlling the mass ratio of the element Si to the element C in the silicon-carbon material within the above range, the carbon skeleton of the silicon-carbon material can be well coated, thereby effectively inhibiting the expansion of silicon particles.
[0059] In one example, in the silicon-carbon material, the mass ratio of element Si to element C is 0.9-1.1.
[0060] In one example, the average particle size of the silicon-carbon material is D2, and D2 is 6 μm-14 μm (for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm or 14 μm).
[0061] According to a specific embodiment, in the silicon-carbon material, the mass ratio of element Si to element C is 0.9-1.1, and the average particle size of the silicon-carbon material is D2, and D2 is 6μm-14μm. Simultaneously controlling the mass ratio of element Si to element C in the silicon-carbon material and the average particle size of the silicon-carbon material is conducive to improving the kinetic performance of the silicon-carbon material, thereby improving the safety performance of the battery.
[0062] In one example, the sphericity of the silicon-carbon material is 0.5 to 1. Controlling the sphericity of the silicon-carbon material within the above range is beneficial to inhibiting the expansion of the silicon-carbon material and reducing the expansion rate of the battery.
[0063] In one example, the average particle size of the silicon-oxygen material is D1, and D1 is 5 μm-15 μm. (For example, 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or 15 μm) In the present invention, the average particle size can be obtained by electron microscopy or laser particle size analyzer. For example, taking the average particle size of the silicon-oxygen material as an example, by SEM, at least 20 silicon-oxygen particles are randomly selected within the field of view of the electron microscope, and the average value is taken to obtain the average particle size of the silicon-oxygen material.
[0064] According to a specific embodiment, m1 is 0.9-1, and the average particle size of the silicon oxide material is D1, and D1 is 5 μm-15 μm. Simultaneously controlling m1 and the average particle size of the silicon oxide material can further improve the dynamic performance of the silicon oxide material.
[0065] In one example, the silicon-oxygen material further includes element Li and / or element Mg. The silicon-oxygen material including element Li and / or element Mg is a silicon-oxygen material that has been chemically pre-lithiated or pre-magnesiated. The silicon-oxygen material treated by this method has active sites on its surface that can chemically react with lithium ions occupied in advance by the pre-lithiation / pre-magnesiation reaction, thereby reducing the side reactions of active lithium on the surface of the silicon-oxygen material located in the surface layer (first negative electrode active material layer), improving the first cycle coulomb efficiency, and increasing the capacity and energy density of the battery.
[0066] In one example, the first negative electrode active material layer includes a first negative electrode active material including the silicon-oxygen material; the second negative electrode active material layer includes a second negative electrode active material including the silicon-carbon material.
[0067] In one example, the first negative electrode active material further includes a first carbon-based material.
[0068] In one example, the mass proportion of the silicon-oxygen material in the first negative electrode active material is ≤20%, and the mass proportion of the first carbon-based particles is ≥80wt%. It is understandable that the mass proportion of the silicon-oxygen material in the first negative electrode active material is not 0, and the mass proportion of the first carbon-based particles is not 100%. At this time, the silicon doping amount in the first negative electrode active material layer is more appropriate, which can improve the energy density of the battery, and will not cause the battery's dynamic performance to decrease due to excessive silicon doping, resulting in excessive expansion of the battery and faster cycle decay.
[0069] In one example, the mass proportion of the silicon oxide material in the first negative electrode active material is 0.1%-10% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%), and the mass proportion of the first carbon-based particles in the first negative electrode active material is 99.9%-90% (for example, 99.9%, 99.5%, 99%, 95% or 90%).
[0070] In one example, the second negative electrode active material further includes a second carbon-based material.
[0071] In one example, the mass proportion of the silicon-carbon material in the second negative electrode active material is ≤15%, and the mass proportion of the second carbon-based particles is ≥85wt%. It is understandable that the mass proportion of the silicon-carbon material in the second negative electrode active material is not 0, and the mass proportion of the second carbon-based particles is not 100%. At this time, the silicon doping amount in the second negative electrode active material layer is more appropriate, which can improve the energy density of the battery, and will not cause the battery's dynamic performance to decrease due to excessive silicon doping, resulting in excessive expansion of the battery and faster cycle decay.
[0072] In one example, the mass proportion of the silicon-carbon material in the second negative electrode active material is 0.1%-8% (for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%), and the mass proportion of the second carbon-based particles in the second negative electrode active material is 99.9%-92% (for example, 99.9%, 99.5%, 99%, 95% or 92%).
[0073] According to a specific implementation, the mass proportion of the silicon-oxygen material in the first negative electrode active material is ≤20%, and the mass proportion of the silicon-carbon material in the second negative electrode active material is ≤15%. At the same time, the mass proportion of the silicon-oxygen material in the first negative electrode active material and the mass proportion of the silicon-carbon material in the second negative electrode active material are controlled. The silicon-oxygen material located on the surface can play its better kinetic performance, preferentially deintercalate lithium during high-rate charging, and can transfer lithium ions to the bottom layer in time; the silicon-carbon material located on the bottom layer can play its advantages of higher gram capacity, lower expansion, and better cycle, provide more lithium insertion sites during the charging process, and reduce the overall expansion of the negative electrode to improve the overall cycle stability of the negative electrode. At the same time, both silicon-oxygen materials and silicon-carbon materials can increase the overall gram capacity of the negative electrode, thereby increasing the energy density of the battery.
[0074] According to a specific implementation, the mass proportion of the silicon-oxygen material in the first negative electrode active material is 0.1%-10%, and the mass proportion of the silicon-carbon material in the second negative electrode active material is 0.1%-8%.
[0075] In one example, the average particle size of the silicon-oxygen material is D1, the average particle size of the silicon-carbon material is D2, the average particle size of the first carbon-based particles is D3, and the average particle size of the second carbon-based particles is D4; satisfying: D3 / D1 is 1.1-2.3 (for example, 1.1, 1.3, 1.5, 1.8, 2, 2.1 or 2.3), D4 / D2 is 1.3-2.6 (for example, 1.3, 1.5, 1.8, 2, 2.3, 2.5 or 2.6). By controlling the ratio of the average particle size of the first carbon-based particles to the average particle size of the silicon-oxygen material and the ratio of the average particle size of the second carbon-based particles to the average particle size of the silicon-carbon material within the above range, it is possible to achieve size matching between the first carbon-based particles and the silicon-oxygen material and size matching between the second carbon-based particles and the silicon-carbon material, thereby forming a good co-embedded environment, that is, the silicon-oxygen material can be effectively filled in the gaps between the first carbon-based particles, and the silicon-carbon material can be effectively filled in the gaps between the second carbon-based particles, thereby improving space utilization and compaction density. At the same time, during charging, the gaps between the first carbon-based particles can provide a buffer space for the expansion of the silicon-oxygen material, and the gaps between the second carbon-based particles can provide a buffer space for the expansion of the silicon-carbon material, thereby reducing the overall expansion of the negative electrode sheet during the charge and discharge cycle, which is beneficial to maintaining the integrity of the negative electrode interface, thereby improving the battery cycle life.
[0076] In one example, D3 / D1 is 1.5-2, and D4 / D2 is 1.6-2.2.
[0077] The first carbon-based particles and the second carbon-based particles may be the same or different, and each independently comprises graphite.
[0078] In one example, the graphite satisfies at least one of the following characteristics:
[0079] (1) an average particle size of 10 μm to 20 μm (e.g., 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm);
[0080] (2) having a coating layer, wherein the coating layer has a thickness of 100 nm to 200 nm (e.g., 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm or 200 nm);
[0081] (3) the interlayer spacing d002 is 0.3 nm to 0.36 nm (e.g., 0.3 nm, 0.31 nm, 0.32 nm, 0.33 nm, 0.34 nm, 0.35 nm or 0.36 nm);
[0082] (4) La is (For example, Lc is (For example, La is the average width of the graphite crystal along the a-axis, in Lc is the thickness of graphite crystals stacked along the c-axis, in units of
[0083] (5) ID / IG is 0.86-1.2 (e.g., 0.86, 0.9, 1, 1.1 or 1.2), ID is the intensity of the D peak in the Raman spectrum, where the D peak is located at 1300 cm -1 -1400cm -1 IG is the intensity of the G peak in the Raman spectrum, where the G peak is located at 1500 cm -1 -1650cm -1 .
[0084] When graphite meets the above preferred conditions, the graphite is liquid-coated graphite, and the surface of the liquid-coated graphite can have a coating layer of moderate thickness, which can improve its cycle stability and is not easy to produce side reactions, and the conduction of lithium ions will not be hindered by the coating layer being too thick; its crystal has a high degree of defects, which can improve its high-rate charge and discharge performance, and at the same time, it will not affect its rate performance due to the long migration path of lithium ions caused by the large grains. At the same time, within this range, after mixing with silicon-carbon materials and silicon-oxygen materials, the expansion of silicon-carbon materials and silicon-oxygen materials can be effectively alleviated (due to liquid-phase coating, the coating is relatively uniform and dense). During the charge and discharge process, the coating layer of the liquid-coated graphite provides a buffer space for the expansion of silicon-carbon materials and silicon-oxygen materials (reducing the damage of silicon-carbon materials and silicon-oxygen materials to graphite particles), while avoiding the destruction of the bonding network and the conductive network, which is conducive to improving the deintercalation of Li and reducing the influence of the expansion of graphite layers on silicon. Controlling La and Lc within the above range can effectively prevent the negative electrode sheet from cracking or peeling off from the negative electrode current collector, which may lead to battery cell failure. At the same time, since the thickness expansion coefficient K0 of the lithium-ion secondary battery is controlled within an appropriate range, a buffer space is provided for the expansion of silicon and graphite, thereby preventing the silicon particles from expanding (too hard) and thus contacting the battery casing, piercing the casing or causing damage to the casing, thereby reducing safety.
[0085] In one example, when the lithium-ion secondary battery is in a 0% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d1, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d2; d1 is 0μm-35μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm or 35μm), and d2 is 0μm-26μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm or 26μm).
[0086] Among them, d1 is the vertical distance from any position on the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the lithium-ion secondary battery is in the SOC state of 0%; d2 is the vertical distance from any position on the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the lithium-ion secondary battery is in the SOC state of 0%.
[0087] In the present invention, d1 and d2 can be obtained by testing by conventional methods in the art, such as using SEM, discharging the lithium-ion secondary battery to a 0% SOC state, taking out the negative electrode sheet, and cutting the negative electrode sheet in the cross-sectional direction, and then observing it under the SEM, measuring the minimum value of the vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer"; and measuring the minimum value of the vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer".
[0088] In one example, d1 is 0 μm-30 μm, and d2 is 0 μm-20 μm;
[0089] In one example, when the lithium-ion secondary battery is in a 100% SOC state, the vertical distance from the surface of the silicon oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d3, and the vertical distance from the surface of the silicon carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d4; d3 is 0μm-40μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm or 40μm), and d4 is 0μm-35μm (for example, 0μm, 0.1μm, 0.5μm, 1μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm or 35μm).
[0090] Among them, d3 is the vertical distance from any position on the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the lithium-ion secondary battery is in a 100% SOC state; d4 is the vertical distance from any position on the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the lithium-ion secondary battery is in a 100% SOC state.
[0091] In the present invention, d3 and d4 can be obtained by testing by conventional methods in the art, such as using SEM, discharging the battery to 100% SOC state, taking out the negative electrode sheet, and cutting the negative electrode sheet in the cross-sectional direction, and then observing it under SEM, measuring the minimum value of the vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer"; and measuring the minimum value of the vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer as the "vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer".
[0092] In one example, d3 is 0 μm-36 μm, and d4 is 0 μm-30 μm.
[0093] According to a specific embodiment, when the lithium-ion secondary battery is in a 0% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d1, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d2; d1 is 0μm-35μm, d2 is 0μm-26μm, and / or, when the lithium-ion secondary battery is in a 100% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d3, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d4; d3 is 0μm-40μm, and d4 is 0μm-35μm.
[0094] By controlling the vertical distance from the surface of the silicon-oxygen material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer and the vertical distance from the surface of the silicon-carbon material to the contact surface between the first negative electrode active material layer and the second negative electrode active material layer when the lithium-ion secondary battery is in a 0% SOC and / or 100% SOC state, the thickness of the first negative electrode active material layer and the second negative electrode active material layer can be controlled within an appropriate range, thereby ensuring that the kinetically superior silicon-oxygen material in the first negative electrode active material layer (surface layer) is in full contact with the electrolyte and can receive the electrolyte. The second negative electrode active material layer (bottom layer) further receives the lithium ions conducted from the first negative electrode active material layer (surface layer), and increases the overall capacity of the negative electrode with its own larger gram capacity. At this time, the negative electrode polarization will not be large and lithium deposition will not occur due to insufficient contact between the active material and the electrolyte due to the excessive thickness of the negative electrode sheet; nor will the negative electrode surface density be low due to the small thickness of the negative electrode sheet, thereby reducing the battery energy density. Therefore, it can ensure that the battery has the advantages of improved lithium deposition and high energy density.
[0095] In the present invention, "the lithium-ion secondary battery is in a 0% SOC state" means that the lithium-ion secondary battery is discharged to the lower limit voltage [for example, 2.75V for ternary high-nickel materials (the molar content of elemental nickel is 80% or more)); "the lithium-ion secondary battery is in a 100% SOC state" means that the lithium-ion secondary battery is charged to the upper limit voltage [for example, 4.2V for ternary high-nickel materials (the molar content of elemental nickel is 80% or more)].
[0096] In one example, d3-d1 is 0μm to 40μm, and d4-d2 is 0μm to 35μm. By controlling the difference between d3 and d1 and the difference between d4 and d2, the expansion of the negative electrode during the charge and discharge process can be controlled within a reasonable range, thereby avoiding excessive expansion resulting in a large distance from the negative electrode surface to the current collector, making it difficult for lithium ions to diffuse to the bottom layer of the negative electrode and causing lithium deposition at the negative electrode.
[0097] In one example, d1 is 0 μm-30 μm, d2 is 0 μm-20 μm, d3 is 0 μm-36 μm, and d4 is 0 μm-30 μm.
[0098] In one example, the surface density of the first negative electrode active material layer is 1 mg / cm 2 -10mg / cm 2 (For example, 1 mg / cm 2 , 2mg / cm 2 、3mg / cm 2 , 4mg / cm 2 , 5mg / cm 2 , 6mg / cm 2 , 7mg / cm 2 , 8mg / cm 2 , 9mg / cm 2 or 10mg / cm 2 ).
[0099] In the present invention, the surface density is a single-sided surface density. Taking the "surface density of the first negative electrode active material layer" as an example, the surface density of the first negative electrode active material layer means that when there is a first negative electrode active material layer on one side of the negative electrode current collector, the surface density of the negative electrode active material layer is the surface density of this side (i.e., the side with the first negative electrode active material layer); when there are first negative electrode active material layers on both sides of the negative electrode current collector, the surface densities of the first negative electrode active material layers on both sides are the same, and the surface density of the first negative electrode active material layer is the surface density of either side.
[0100] In one example, the porosity of the first negative active material layer is 30%-45% (eg, 30%, 32%, 35%, 38%, 40%, 42% or 45%).
[0101] In one example, the surface density of the second negative electrode active material layer is 0.5 mg / cm 2 -6mg / cm 2 (For example, 0.5 mg / cm 2 , 1mg / cm 2 , 1.5mg / cm 2 , 2mg / cm 2 , 2.5mg / cm 2 、3mg / cm2 、3.5mg / cm 2 , 4mg / cm 2 , 4.5mg / cm 2 , 5mg / cm 2 , 5.5mg / cm 2 or 6mg / cm 2 ).
[0102] In one example, the porosity of the second negative active material layer is 25%-40% (eg, 25%, 28%, 30%, 32%, 35%, 38% or 40%).
[0103] In one example, the surface density of the first negative electrode active material layer is 1 mg / cm 2 -10mg / cm 2 , and the surface density of the second negative electrode active material layer is 0.5 mg / cm 2 -6mg / cm 2 . Controlling the surface density of the first negative electrode active material layer and the surface density of the second negative electrode active material layer can take into account both energy density and fast charging performance. At this time, the negative electrode sheet will not increase polarization and deteriorate fast charging capability due to surface density, nor will it cause insufficient energy density due to too low surface density; at the same time, the surface density of the first negative electrode active material layer is appropriately higher than the surface density of the second negative electrode active material layer, so that the silicon oxide material in the first negative electrode active material layer can accommodate as many lithium ions as possible during the fast charging process and conduct them to the second negative electrode active material layer, so that the battery has the advantages of high energy density and good fast charging performance.
[0104] In one example, the compaction density of the negative electrode sheet is 1.5 g / cm 3 -1.7g / cm 3 (For example, 1.5 g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 or 1.7 g / cm 3 ). The compaction density of the negative electrode sheet is the overall compaction density of the negative electrode sheet.
[0105] In one example, the porosity of the first negative electrode active material layer is 30%-45%, the porosity of the second negative electrode active material layer is 25%-40%, and the compaction density of the negative electrode sheet is 1.5 g / cm 3 -1.7g / cm 3The relatively high porosity of the first negative electrode active material layer can promote the electrolyte to infiltrate the inside of the electrode, which is beneficial to the rapid transmission of lithium ions. The relatively slightly lower porosity of the second negative electrode active material layer can improve the space utilization, reduce the overall thickness of the negative electrode, and improve the energy density of the battery. At the same time, the compaction density of the negative electrode sheet is controlled within the above range to ensure close contact between the particles of silicon-oxygen material and carbon-based material, as well as close contact between the particles of silicon-carbon material and carbon-based material, thereby forming an effectively cross-linked conductive network and improving the fast charging performance of the battery. At this time, the electrolyte will not infiltrate the inside of the negative electrode sheet poorly due to the excessively high compaction density of the negative electrode sheet, hindering the transmission of lithium ions and reducing the fast charging performance of the battery.
[0106] In one example, the negative electrode current collector includes a metal layer and a primer layer located on at least one side of the metal layer, and the thickness of the primer layer is 0.5 μm-2 μm. When the negative electrode current collector includes a primer layer, the peel strength between the second negative electrode active material layer and the negative electrode current collector can be effectively improved, and the bonding effect between the second negative electrode active material layer and the negative electrode current collector can be enhanced, thereby improving the cycle performance of the battery. The present invention does not limit the specific components of the primer layer, and the primer layer conventionally used in the art can be selected. For example, the primer layer can include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), conductive carbon black, graphene, and carbon nanotubes.
[0107] In one example, the metal layer includes copper foil.
[0108] In one example, the first negative electrode active material layer further includes a first binder, and the second negative electrode active material layer further includes a second binder.
[0109] In one example, the first binder includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, polyacrylonitrile, polyacrylamide, polymethacrylate, alginic acid, alginate, polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0110] In one example, the second binder includes one or more of styrene-butadiene rubber (SBR), polyacrylic acid, polyacrylic acid salt, polyvinyl alcohol, polyacrylonitrile, polyacrylamide, polymethacrylate, alginic acid, alginate, polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF).
[0111] In one example, the first binder and the second binder are the same or different.
[0112] In one example, the first binder and the second binder both include styrene-butadiene rubber. When the first binder and the second binder both include styrene-butadiene rubber, the compatibility between the slurry of the first negative electrode active material layer and the slurry of the second negative electrode active material layer is optimal during coating, and the two layers of slurry will not shrink at the edges due to poor compatibility during coating, nor will the upper and lower layers be mixed, and after baking, the first negative electrode active material layer and the second negative electrode active material layer will not be peeled off.
[0113] In one example, the first negative electrode active material layer includes a first negative electrode active material, and the first negative electrode active material includes a silicon-oxygen material and first carbon-based particles.
[0114] In one example, the first negative electrode active material layer further includes a first conductive agent and a first thickener.
[0115] In one example, the first conductive agent includes one or more of conductive carbon black (SP), Ketjen black, acetylene black, graphite conductive agent (KS-6, KS-15, SO, SEG-6), carbon fiber (VGCG), carbon nanotube (CNT) and graphene.
[0116] In one example, the first thickener includes one or more of carboxymethyl cellulose (CMC), lithium carboxymethyl cellulose (CMCLi) and sodium carboxymethyl cellulose (CMCNa).
[0117] In one example, based on the total weight of the first negative electrode active material layer, the weight content of the first negative electrode active material is 93%-99.7% (for example, 93%, 94%, 95%, 96%, 97%, 98% or 99.7%), the weight content of the first conductive agent is 0.1%-1% (for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%), the weight content of the first binder is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%), and the first thickener is 0.1%-3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3%).
[0118] In one example, the second negative electrode active material layer includes a second negative electrode active material, and the second negative electrode active material includes a silicon-carbon material and second carbon-based particles.
[0119] In one example, the second negative electrode active material layer further includes a second conductive agent and a second thickener.
[0120] In one example, the second conductive agent includes one or more of conductive carbon black (SP), Ketjen black, acetylene black, graphite conductive agents (KS-6, KS-15, S-O, SEG-6), carbon fiber (VGCG), carbon nanotube (CNT), and graphene.
[0121] The first conductive agent and the second conductive agent may be the same or different.
[0122] The first thickening agent and the second thickening agent may be the same or different.
[0123] In one example, the second thickening agent includes one or more of carboxymethyl cellulose (CMC), lithium carboxymethyl cellulose (CMCLi), and sodium carboxymethyl cellulose (CMCNa).
[0124] In one example, based on the total weight of the second negative electrode active material layer, the weight content of the second negative electrode active material is 93% - 99.7% (for example, 93%, 94%, 95%, 96%, 97%, 98%, or 99.7%), the weight content of the second conductive agent is 0.1% - 1% (for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or 1%), the weight content of the second binder is 0.1% - 3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%), and the second thickening agent is 0.1% - 3% (for example, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, or 3%).
[0125] In one example, the lithium ion secondary battery further includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a nickel-cobalt-manganese ternary material.
[0126] In one example, the nickel-cobalt-manganese ternary material includes a substance with the chemical formula Li a Ni x Co y Mn z A k O2, where 0.9 ≤ a ≤ 1.2 (for example, 0.9, 0.95, 1, 1.05, 1.1, or 1.2), 0.8 ≤ x ≤ 0.95 (for example, 0.8, 0.85, 0.9, or 0.95), 0 < y ≤ 0.2 (for example, 0.01, 0.05, 0.1, 0.15, or 0.2), 0 < z ≤ 0.2 (for example, 0.01, 0.05, 0.1, 0.15, or 0.2), 0 ≤ k ≤ 0.05 (for example, 0, 0.01, 0.02, 0.03, 0.04, or 0.05), and A is selected from at least one of Al, Zr, B, Y, Sr, W, Mg, Fe, Ti, and Nb.
[0127] Wherein, A is a doping element, and when k is 0, it indicates that the positive electrode active material does not include the doping element A.
[0128] In one example, 0.9≤x≤0.95.
[0129] In one example, the positive electrode active material has a layered structure.
[0130] In one example, the nickel-cobalt-manganese ternary material includes single crystal particles, and the single crystal particles contain element B.
[0131] In one example, the mass content of element B in the single crystal particles is 200ppm-1000ppm (for example, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm or 1000ppm). Controlling the mass content of element B in the single crystal particles within the above range can enhance the structural stability of the nickel-cobalt-manganese ternary material, thereby improving the cycle life and capacity of the positive electrode sheet.
[0132] In one example, the positive electrode active material includes single crystal particles and polycrystalline particles, and the mass ratio of the polycrystalline particles to the single crystal particles is 2.33-4 (for example, 2.33, 2.5, 3, 3.5 or 4). In this case, the positive electrode active material is a mixture of single crystal particles and polycrystalline particles, and the polycrystalline particles are mainly used, so that the positive electrode sheet has good cycle and rate performance, and the high rate and charge and discharge performance of the battery will not be insufficient due to too many single crystal particles, and the battery cycle performance will not be affected by too many side reactions on the positive electrode interface due to too many polycrystalline particles.
[0133] In one example, the ratio of the areal density of the positive electrode sheet to the areal density of the negative electrode sheet is 1.5-2.5 (e.g., 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4 or 2.5).
[0134] In the present invention, the surface density of the negative electrode sheet is the sum of the surface density of the first negative electrode active material layer and the surface density of the second negative electrode active material layer.
[0135] In one example, the ratio of the surface density of the positive electrode sheet to the surface density of the negative electrode sheet is 1.7-2.3.
[0136] In one example, the positive electrode sheet and the negative electrode sheet are stacked. It is understandable that the positive electrode sheet and the negative electrode sheet are stacked to form a core, and a separator is provided between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet from the negative electrode sheet.
[0137] In one example, the positive electrode sheet includes: a positive electrode current collector; and a plurality of (e.g., ≥2) positive electrode tabs extending from one edge of the positive electrode current collector. In this case, the number of positive electrode tabs is ≥2. Since the nickel-cobalt-manganese ternary material and the silicon-carbon material system generate more heat, controlling the number of positive electrode tabs within the above range is beneficial to heat dissipation, thereby improving the safety performance of the lithium-ion secondary battery.
[0138] In one example, a positive electrode active material layer is located on at least one side of the positive electrode collector; and a ceramic layer is located on the edge surface of the positive electrode collector having the positive electrode tab side; the ceramic layer is in contact with the positive electrode active material layer.
[0139] In one example, the positive electrode active material layer includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.
[0140] In one example, the positive electrode conductive agent includes at least one of conductive carbon black (SP), Ketjen black, acetylene black, graphite conductive agent (KS-6, KS-15, SO, SEG-6), carbon fiber (VGCG), carbon nanotube (CNT) and graphene.
[0141] In one example, the positive electrode binder includes one or more of PVDF, PVDF-HFP, polytetrafluoroethylene, polyacrylonitrile, polyimide and perfluorosulfonic acid ionomer binders.
[0142] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 92%-98% (for example, 92%, 93%, 94%, 95%, 96%, 97% or 98%), the weight content of the positive electrode conductor is 1%-4% (for example, 1%, 2%, 3% or 4%), and the weight content of the positive electrode binder is 1%-4% (for example, 1%, 2%, 3% or 4%).
[0143] In one example, the lithium-ion secondary battery further includes an electrolyte, and the electrolyte is located in the accommodation space.
[0144] In one example, the electrolyte includes fluoroethylene carbonate.
[0145] In one example, the mass content of fluoroethylene carbonate in the electrolyte is 3%-25% (for example, 3%, 5%, 10%, 15%, 20% or 25%). Controlling the mass content of fluoroethylene carbonate in the electrolyte within the above range can promote the electrolyte to form a dense and stable SEI film on the surface of the negative electrode sheet. The SEI film can block further electrochemical reactions between the electrolyte and the negative electrode, thereby facilitating the interface between the negative electrode sheet and the electrolyte to remain stable, preventing the electrolyte from being continuously consumed, and improving the cycle life of the battery.
[0146] In one example, the electrolyte further includes a lithium salt and an organic solvent.
[0147] In one example, the electrolyte includes a lithium salt and an organic solvent, and the lithium salt includes one or more of lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, lithium difluorophosphate (LiPO2F2), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium tetrafluoroborate (LiBF4), lithium difluorobis(oxalatoborate) (LiDFOP) and lithium bis(trifluoromethylsulfonyl)imide.
[0148] In one example, the organic solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), dimethyl carbonate (DEC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, diethyl carbonate (DMC), ethyl formate, ethyl acetate (EA), ethyl propionate (EP) and propyl propionate (PP).
[0149] In one example, the concentration of the lithium salt in the electrolyte is 10%-15% (eg, 10%, 11%, 12%, 13%, 14% or 15%).
[0150] In one example, based on the total weight of the electrolyte, the mass content of the organic solvent is 65%-87% (e.g., 65%, 68%, 70%, 73%, 75%, 78%, 80%, 83%, 85% or 87%).
[0151] In one example, the CB value of the lithium-ion secondary battery is 1.1-1.2 (for example, 1.1, 1.12, 1.15, 1.18 or 1.2). The CB value is the ratio of the theoretical capacity of the negative electrode of the battery to the theoretical capacity of the positive electrode. By controlling the CB value within the above range, the battery will not have insufficient fast charging capability due to a too low CB value, nor will the battery energy density be low due to a too high CB value.
[0152] In one example, the CB value of the lithium-ion secondary battery is 1.11-1.14.
[0153] Research has found that for square or cylindrical batteries, too high anode expansion rate is not conducive to maintaining the structural stability of the battery. Excessive expansion of the internal stacked core / rolled core can easily cause the battery to swell and deform, leading to battery failure. The adaptability of the dimensions of the battery cell and the shell in the thickness direction of the present invention is relatively high, which can overcome the problem that the internal stacked core / rolled core expansion is too high and can easily cause the battery to swell and deform. Therefore, the lithium-ion secondary battery of the present invention is more suitable for square or cylindrical batteries.
[0154] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0155] In the following examples, unless otherwise specified, all materials used were commercially available analytical grade.
[0156] The following examples are used to illustrate the negative electrode sheet and lithium ion secondary battery of the present invention.
[0157] Example 1
[0158] The lithium ion secondary battery was prepared as follows:
[0159] (1) Preparation of negative electrode
[0160] Preparation of ingredients: First negative electrode active material layer: 95 parts by weight of the first negative electrode active material (wherein the weight ratio of the silicon-oxygen material to the first carbon-based particles (liquid-phase coated graphite) is 13:87, wherein the silicon-oxygen ratio m1 in the silicon-oxygen material is 0.95, the silicon-oxygen material includes element Mg, the mass content of element Mg in the silicon-oxygen material is 800ppm, the thickness of the carbon cross section on the surface of the silicon-oxygen material is 100nm, and the average particle size D1 of the silicon-oxygen material is 10μm; the average particle size D3 of the first carbon-based particles is 16μm, the thickness of the coating layer of the liquid-phase coated graphite is 145nm, the interlayer spacing d002 is 0.339nm, and La is Lc is ID / IG is 1.04), 0.5 parts by weight of a first conductive agent (conductive carbon black), 2.5 parts by weight of a first binder (SBR), and 2 parts by weight of a first thickener (carboxymethyl cellulose lithium (CMCLi));
[0161] Second negative electrode active material layer: 95 parts by weight of the second negative electrode active material (wherein the weight ratio of the silicon-carbon material to the second carbon-based particles (liquid-phase coated graphite) is 11:89, wherein the silicon-oxygen ratio m2 in the silicon-carbon material is 30, the silicon-carbon ratio in the silicon-carbon material is 1.05, and the average particle size D2 of the silicon-carbon material is 8 μm; the average particle size D4 of the second carbon-based particles is 16 μm, the thickness of the coating layer of the liquid-phase coated graphite is 154 nm, the interlayer spacing d002 is 0.331 nm, and La is Lc is ID / IG is 1.13), 0.5 parts by weight of a second conductive agent (conductive carbon black), 2.5 parts by weight of a second binder (SBR), and 2 parts by weight of a second thickener (carboxymethyl cellulose lithium (CMCLi)).
[0162] Preparation: a first negative electrode active material, a first thickener, a first binder and a first conductive agent are mixed, and a uniformly dispersed mixture is obtained by high-speed stirring, and water is used as a solvent to prepare a slurry of the first negative electrode active material layer, wherein the solid content in the slurry is 50wt%;
[0163] The second negative electrode active material, the second thickener, the second binder and the second conductive agent are mixed, stirred at high speed to obtain a uniformly dispersed mixture, and water is used as a solvent to prepare a slurry of the second negative electrode active material layer, wherein the solid content in the slurry is 50 wt %.
[0164] During coating, the first negative electrode active material layer and the second negative electrode active material layer slurry should be placed in the upper and lower pipes of the double-layer extrusion coater respectively, and sprayed evenly on one side of the negative electrode current collector copper foil to form two wet films, where the surface density of the first negative electrode active material layer and the second negative electrode active material layer are 4.5 mg / cm 2 and 3.3 mg / cm 2 , then baked to obtain a single-sided negative electrode, and coated the other side in the same way to form a double-sided, and then baked and rolled to obtain a negative electrode sheet. Among them, the porosity of the first negative electrode active material layer is 36%, and the porosity of the second negative electrode active material layer is 32%. Among them, m1 / m2 is 0.03167, D3 / D1 is 1.6, D4 / D2 is 2, d1 is 0-25μm, d2 is 0-18μm, d3 is 0-35μm, d4 is 0-25μm, d3-d1 is 0-35μm, d4-d2 is 0-25μm, and the negative electrode current collector contains a primer layer.
[0165] (2) Preparation of positive electrode
[0166] Component preparation: Positive electrode active material: Nickel-cobalt-manganese ternary material (wherein, the nickel-cobalt-manganese ternary material is a single crystal particle with a chemical formula of LiNi 0.92 Co 0.02 Mn 0.04 Al 0.02 O2, the mass content of element B is 543ppm), 97 parts by weight, positive electrode binder: PVDF, 1.5 parts by weight, positive electrode conductor: conductive carbon black, 1.5 parts by weight;
[0167] The positive electrode active material, positive electrode binder and positive electrode conductive agent are mixed, stirred at high speed to obtain a uniformly dispersed mixture, and NMP is used as a solvent to prepare a positive electrode active material slurry, the solid content of the slurry is 70wt%. The slurry is evenly coated on the surfaces of both sides of the positive electrode collector, dried, and rolled to obtain a positive electrode sheet. The surface density ratio of the positive electrode sheet to the negative electrode sheet is 1.9.
[0168] (3) Preparation of electrolyte
[0169] Organic solvent: ethylene carbonate, 45 parts by weight, diethyl carbonate, 40 parts by weight.
[0170] In a glove box filled with argon (H2O < 0.1ppm, O2 < 0.1ppm), the organic solvent and fluoroethylene carbonate (wherein the mass content of fluoroethylene carbonate in the electrolyte is 5%) are evenly mixed, and then fully dried lithium salt (10 parts by weight) is quickly added thereto to obtain the desired electrolyte.
[0171] (4) Diaphragm
[0172] The diaphragm substrate is 9μm, the single-sided ceramic is 2μm, and the double-sided glue layer is 1μm on each side. The glue is oil-based coating.
[0173] (5) Preparation of lithium-ion batteries
[0174] The positive electrode sheet of step (1), the negative electrode sheet of step (2) and the separator of step (4) are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, the electrolyte of step (3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The CB value of the lithium ion battery is 1.12.
[0175] Where, T0 is 22.5 mm, T is 25 mm, K0 = (22.5 / 25) × 100% = 90%, T 100 24.4mm, K 100 =(24.4 / 25)×100%=97.6%; H 100 is 118.7μm, H is 90μm, R 100 =[(118.7-90) / 90]×100%=31.9%, H0 is 93.1μm, R0=[(93.1-90) / 90]×100%=3.44%.
[0176] Example 2
[0177] (1) Preparation of negative electrode
[0178] Preparation of ingredients: First negative electrode active material layer: 95 parts by weight of the first negative electrode active material (wherein the weight ratio of the silicon-oxygen material to the first carbon-based particles (liquid-phase coated graphite) is 13:87, wherein the silicon-oxygen ratio m1 in the silicon-oxygen material is 0.95, the silicon-oxygen material includes element Mg, the mass content of element Mg in the silicon-oxygen material is 429 ppm, the thickness of the carbon cross section on the surface of the silicon-oxygen material is 86 nm, and the average particle size D1 of the silicon-oxygen material is 7 μm; the average particle size D3 of the first carbon-based particles is 12 μm, the thickness of the coating layer of the liquid-phase coated graphite is 122 nm, the interlayer spacing d002 is 0.351 nm, and La is Lc is ID / IG is 0.92), 0.5 weight parts of the first conductive agent (conductive carbon black), 2.5 weight parts of the first binder (SBR), and 2 weight parts of the first thickener (carboxymethyl cellulose lithium (CMCLi)); the surface density of the first negative electrode active material layer is 4.2 mg / cm 2 ;
[0179] Second negative electrode active material layer: 95 parts by weight of the second negative electrode active material (wherein the weight ratio of the silicon-carbon material to the second carbon-based particles (liquid-phase coated graphite) is 11:89, wherein the silicon-oxygen ratio m2 in the silicon-carbon material is 43.8, the silicon-carbon ratio in the silicon-carbon material is 0.98, and the average particle size D2 of the silicon-carbon material is 9 μm; the average particle size D4 of the second carbon-based particles is 11 μm, the thickness of the coating layer of the liquid-phase coated graphite is 113 nm, the interlayer spacing d002 is 0.354 nm, and La is Lc is ID / IG is 0.89), 0.5 parts by weight of the second conductive agent (conductive carbon black), 2.5 parts by weight of the second binder (SBR), and 2 parts by weight of the second thickener (carboxymethyl cellulose lithium (CMCLi)). The surface density of the second negative electrode active material layer is 3.1 mg / cm 2 ;
[0180] Among them, m1 / m2 is 0.02169, D3 / D1 is 1.71, D4 / D2 is 1.22, d1 is 0-28μm, d2 is 0-20μm, d3 is 0-38μm, d4 is 0-32μm, d3-d1 is 0-38μm, d4-d2 is 0-35μm, and the negative electrode current collector contains a primer layer.
[0181] Preparation: Same as Example 1;
[0182] (2) Preparation of positive electrode
[0183] Component preparation: Positive electrode active material: Nickel-cobalt-manganese ternary material (wherein, the nickel-cobalt-manganese ternary material is a single crystal particle with a chemical formula of LiNi 0.92 Co 0.02 Mn 0.04 Al 0.02 O2, the mass content of element B is 371ppm), 97 parts by weight, positive electrode binder: PVDF, 1.5 parts by weight, positive electrode conductor: conductive carbon black, 1.5 parts by weight;
[0184] The preparation was the same as in Example 1. The ratio of the surface density of the positive electrode sheet to the negative electrode sheet was 2.2.
[0185] (3) The preparation of the electrolyte is the same as in Example 1.
[0186] (4) The diaphragm is the same as in Example 1.
[0187] (5) The preparation of lithium-ion battery is the same as that in Example 1.
[0188] Among them, T0 is 22.8mm, T is 25mm, K0=(22.8 / 25)×100%=91.2%, T 100 24mm, K 100 =(24 / 25)×100%=96%; H 100 is 124.6μm, H is 90μm, R 100 =[(124.6-90) / 90]×100%=38.4%, H0 is 91.7μm, R0=](91.7-90) / 90]×100%=1.89%.
[0189] Example 3
[0190] (1) Preparation of negative electrode
[0191] Preparation of ingredients: First negative electrode active material layer: 95 parts by weight of the first negative electrode active material (wherein the weight ratio of the silicon-oxygen material to the first carbon-based particles (liquid-phase coated graphite) is 13:87, wherein the silicon-oxygen ratio m1 in the silicon-oxygen material is 1.02, the silicon-oxygen material includes element Mg, the mass content of element Mg in the silicon-oxygen material is 5871 ppm, the thickness of the carbon cross section on the surface of the silicon-oxygen material is 158 nm, and the average particle size D1 of the silicon-oxygen material is 11 μm; the average particle size D3 of the first carbon-based particles is 14 μm, the thickness of the coating layer of the liquid-phase coated graphite is 187 nm, the interlayer spacing d002 is 0.309 nm, and La is Lc is ID / IG is 1.16), 0.5 weight parts of the first conductive agent (conductive carbon black), 2.5 weight parts of the first binder (SBR), and 2 weight parts of the first thickener (carboxymethyl cellulose lithium (CMCLi)); the surface density of the first negative electrode active material layer is 4.7 mg / cm 2 ;
[0192] Second negative electrode active material layer: 95 parts by weight of the second negative electrode active material (wherein the weight ratio of the silicon-carbon material to the second carbon-based particles (liquid-phase coated graphite) is 11:89, wherein the silicon-oxygen ratio m2 in the silicon-carbon material is 382, the silicon-carbon ratio in the silicon-carbon material is 1.14, and the average particle size D2 of the silicon-carbon material is 7 μm; the average particle size D4 of the second carbon-based particles is 14 μm, the thickness of the coating layer of the liquid-phase coated graphite is 191 nm, the interlayer spacing d002 is 0.313 nm, and La is Lc is ID / IG is 1.19), 0.5 parts by weight of the second conductive agent (conductive carbon black), 2.5 parts by weight of the second binder (SBR), and 2 parts by weight of the second thickener (carboxymethyl cellulose lithium (CMCLi)). The surface density of the second negative electrode active material layer is 2.8 mg / cm 2 ;
[0193] Among them, m1 / m2 is 0.00267, D3 / D1 is 1.27, D4 / D2 is 2, d1 is 0-32μm, d2 is 0-26μm, d3 is 0-40μm, d4 is 0-35μm, d3-d1 is 0-40μm, d4-d2 is 0-35μm, and the negative electrode current collector contains a primer layer.
[0194] Preparation: Same as Example 1;
[0195] (2) Preparation of positive electrode
[0196] Component preparation: Positive electrode active material: Nickel-cobalt-manganese ternary material (wherein, the nickel-cobalt-manganese ternary material is a single crystal particle with a chemical formula of LiNi 0.92 Co 0.02 Mn 0.04 Al 0.02 O2, the mass content of element B is 828ppm), 97 parts by weight, positive electrode binder: PVDF, 1.5 parts by weight, positive electrode conductor: conductive carbon black, 1.5 parts by weight;
[0197] The preparation was the same as in Example 1. The ratio of the surface density of the positive electrode sheet to the negative electrode sheet was 2.4.
[0198] (3) The preparation of the electrolyte is the same as in Example 1.
[0199] (4) The diaphragm is the same as in Example 1.
[0200] (5) The preparation of lithium-ion battery is the same as that in Example 1.
[0201] Where, T0 is 21.7 mm, T is 25 mm, K0 = (21.7 / 25) × 100% = 86.8%, T 100 24.8mm, K 100 =(24.8 / 25)×100%=99.2%; H 100 is 129.9μm, H is 90μm, R 100 =[(129.9-90) / 90]×100%=44.3%, H0 is 95.4μm, R0=[(95.4-90) / 90]×100%=6%.
[0202] Example 4 Group
[0203] This group of embodiments is used to illustrate the impact when the mass content of m1 or m2 or element Mg in the silicon-oxygen material changes.
[0204] Example 4a
[0205] The same process is carried out as in Example 1, except that m1 is 0.82 and m1 / m2 is 0.02733.
[0206] Example 4b
[0207] The same process is carried out as in Example 1, except that m1 is 1.17 and m1 / m2 is 0.039.
[0208] Example 4c
[0209] The same process is carried out as in Example 1, except that m1 is 0.73 and m1 / m2 is 0.02433.
[0210] Example 4d
[0211] The same process is carried out as in Example 1, except that m1 is 1.31 and m1 / m2 is 0.04367.
[0212] Example 4e
[0213] The process is carried out in accordance with Example 1, except that m2 is 21.4, the silicon-carbon ratio in the silicon-carbon material is 0.92, and m1 / m2 is 0.04439.
[0214] Example 4f
[0215] The process is carried out in accordance with Example 1, except that m2 is 8.1, the silicon-carbon ratio in the silicon-carbon material is 0.85, and m1 / m2 is 0.11728.
[0216] Example 4g
[0217] The process is carried out in accordance with Example 1, except that m2 is 486, the silicon-carbon ratio in the silicon-carbon material is 1.2, and m1 / m2 is 0.00195.
[0218] Example 4h
[0219] The process is carried out in accordance with Example 1, except that m2 is 5.4, the silicon-carbon ratio in the silicon-carbon material is 0.53, and m1 / m2 is 0.17593.
[0220] Example 4i
[0221] The process is carried out in accordance with Example 1, except that m2 is 1489, the silicon-carbon ratio in the silicon-carbon material is 1.66, and m1 / m2 is 0.00064.
[0222] Embodiment 4j
[0223] The process is carried out in accordance with Example 1, except that the mass content of element Mg in the silicon-oxygen material is 284 ppm.
[0224] Embodiment 4k
[0225] The process is carried out in accordance with Example 1, except that the mass content of element Mg in the silicon-oxygen material is 9875 ppm.
[0226] Example 5 Group
[0227] This group of examples is used to illustrate the effects of changes in D3 / D1 and / or D4 / D2, wherein d1, d2, d3 and d4 can be kept constant by adjusting the porosity.
[0228] Example 5a
[0229] The process is carried out in accordance with Example 1, except that the average particle size D1 of the silicon oxide material is 8 μm, and D3 / D1 is 2.
[0230] Example 5b
[0231] The process is carried out in accordance with Example 1, except that the average particle size D3 of the first carbon-based particles is 10 μm, and D3 / D1 is 1.
[0232] Example 5c
[0233] The process is carried out in accordance with Example 1, except that the average particle size D1 of the silicon-oxygen material is 12 μm, the average particle size D3 of the first carbon-based particles is 10 μm, and D3 / D1 is 0.83.
[0234] Example 5d
[0235] The process is carried out in accordance with Example 1, except that the average particle size D4 of the second carbon-based particles is 13 μm, and D4 / D2 is 1.63.
[0236] Example 5e
[0237] The process is carried out in accordance with Example 1, except that the average particle size D4 of the second carbon-based particles is 20 μm, and D4 / D2 is 2.5.
[0238] Example 5f
[0239] The process is carried out in accordance with Example 1, except that the average particle size D4 of the second carbon-based particles is 11 μm, and D4 / D2 is 1.38.
[0240] Example 5g
[0241] The process is carried out in accordance with Example 1, except that the average particle size D2 of the silicon-carbon material is 14 μm, and D4 / D2 is 1.14.
[0242] Example 5h
[0243] Refer to Example 1, except that the average particle size D1 of the silicon-oxygen material is 11 μm, the average particle size D3 of the first carbon-based particles is 10 μm, the average particle size D2 of the silicon-carbon material is 6 μm, the average particle size D4 of the second carbon-based particles is 20 μm, D3 / D1 is 0.91, and D4 / D2 is 3.33.
[0244] Example 6 Group
[0245] This group of examples is used to illustrate the effects produced when the chemical formula of the nickel-cobalt-manganese ternary material is changed.
[0246] Example 6a
[0247] The same method as in Example 1 is used, except that the chemical formula of the nickel-cobalt-manganese ternary material is LiNi 0.6 Co 0.18 Mn 0.21 Al 0.01 O2.
[0248] Example 6b
[0249] The same method as in Example 1 is used, except that the chemical formula of the nickel-cobalt-manganese ternary material is LiNi 0.85 Co 0.09 Mn 0.05 Al 0.01 O2.
[0250] Example 7 Group
[0251] This group of embodiments is used to illustrate the impact when d1 and / or d3 are changed.
[0252] Example 7a
[0253] The method is carried out in accordance with Example 1, except that d1 is 0-33 μm, d3 is 0-39 μm, d3-d1 is 0-39 μm, and the surface density of the first negative electrode active material layer is 4.7 mg / cm 2 The surface density ratio of the positive electrode sheet to the negative electrode sheet is 1.85.
[0254] Example 7b
[0255] The method is carried out in accordance with Example 1, except that d1 is 0-40 μm, d3 is 0-44 μm, d3-d1 is 0-44 μm, and the surface density of the first negative electrode active material layer is 5.5 mg / cm 2 The ratio of the surface density of the positive electrode sheet to the negative electrode sheet is 1.68.
[0256] Example 8 Group
[0257] This group of embodiments is used to illustrate the impact when d2 and / or d4 are changed.
[0258] Example 8a
[0259] The method is carried out in accordance with Example 1, except that d2 is 0-24 μm, d4 is 0-35 μm, d4-d2 is 0-35 μm, and the surface density of the second negative electrode active material layer is 3.5 mg / cm 2 The ratio of the surface density of the positive electrode sheet to the negative electrode sheet is 1.65.
[0260] Example 8b
[0261] The method is carried out in accordance with Example 1, except that d2 is 0-30 μm, d4 is 0-41 μm, d4-d2 is 0-41 μm, and the surface density of the second negative electrode active material layer is 4 mg / cm 2 The ratio of the surface density of the positive electrode sheet to the negative electrode sheet is 1.74.
[0262] Example 9
[0263] The same procedure is carried out as in Example 1, except that the negative electrode current collector has no undercoat layer.
[0264] Example 10 Group
[0265] This group of embodiments is used to illustrate the impact produced when the thickness of the carbon layer on the surface of the silicon-oxygen material changes.
[0266] Example 10a
[0267] The process is carried out in accordance with Example 1, except that the thickness of the carbon layer on the surface of the silicon-oxygen material is 26 nm.
[0268] Example 10b
[0269] The process is carried out in accordance with Example 1, except that the thickness of the carbon layer on the surface of the silicon-oxygen material is 184 nm.
[0270] Example 11 Group
[0271] This group of embodiments is used to illustrate that when K0 and / or K 100 and / or R0 and / or R 100 The impact of changes when they occur.
[0272] Example 11a
[0273] The same method as in Example 1 is used, except that T0 is 23 mm, T is 25 mm, K0 = (23 / 25) × 100% = 92%, T 100 24.7mm, K 100 =(24.7 / 25)×100%=98.8%; H 100126μm, H 90μm, R 100 =((126 / 90)-1)×100%=40%, H0 is 94.4μm, R0=((94.4 / 90)-1)×100%=4.89%.
[0274] Example 11b
[0275] Refer to Example 1, except that T0 is 22.3 mm, T is 25 mm, K0 = (22.3 / 25) × 100% = 89.2%, T 100 24.3mm, K 100 =(24.3 / 25)×100%=97.2%; H 100 is 112.7μm, H is 90μm, R 100 =((112.7 / 90)-1)×100%=25.2%, H0 is 90.5μm, R0=((90.5 / 90)-1)×100%=0.56%.
[0276] Example 11c
[0277] Refer to Example 1, except that T0 is 21.3 mm, T is 25 mm, K0 = (21.3 / 25) × 100% = 85.2%, T 100 23.8mm, K 100 =(23.8 / 25)×100%=95.2%; H 100 is 97.3μm, H is 90μm, R 100 =((97.3 / 90)-1)×100%=8.1%, H0 is 90.2μm, R0=((90.2 / 90)-1)×100%=0.22%.
[0278] Example 11d
[0279] Refer to Example 1, except that T0 is 23.2 mm, T is 25 mm, K0 = (23.2 / 25) × 100% = 92.8%, T 100 24.9mm, K 100 =(24.9 / 25)×100%=99.6%; H 100 is 130.4μm, H is 90μm, R 100 =((130.4 / 90)-1)×100%=44.9%, H0 is 96.3μm, R0=((96.3 / 90)-1)×100%=7%.
[0280] Example 11e
[0281] The same method as in Example 1 is used, except that T0 is 21.5 mm, T is 25 mm, K0 = (21.5 / 25) × 100% = 86%, T 100 23.3mm, K 100 =(23.3 / 25)×100%=93.2%; H 100 is 96.2μm, H is 90μm, R 100 =((96.2 / 90)-1)×100%=6.9%, H0 is 90.3μm, R0=((90.3 / 90)-1)×100%=0.33%.
[0282] Example 12 Group
[0283] This group of examples is used to illustrate the effects produced when the mass content of element B in a single crystal particle changes.
[0284] Example 12a
[0285] The process is carried out in accordance with Example 1, except that the mass content of element B in the single crystal particles is 214 ppm.
[0286] Example 12b
[0287] The process is carried out in accordance with Example 1, except that the mass content of element B in the single crystal particles is 988 ppm.
[0288] Example 12c
[0289] The process is carried out in accordance with Example 1, except that the mass content of element B in the single crystal particles is 0 ppm.
[0290] Example 12d
[0291] The process is carried out in accordance with Example 1, except that the mass content of element B in the single crystal particles is 1245 ppm.
[0292] Embodiment 13
[0293] The process is carried out in accordance with Example 1, except that the nickel-cobalt-manganese ternary material is polycrystalline particles.
[0294] Example 14 Group
[0295] This group of embodiments is used to illustrate the effects produced when the first carbon-based particles and / or the second carbon-based particles are changed.
[0296] Example 14a
[0297] The method is carried out in accordance with Example 1, except that the first carbon-based particle is liquid-coated graphite, the coating layer of the liquid-coated graphite has a thickness of 103 nm, an interlayer spacing d002 of 0.302 nm, and La is Lc is ID / IG is 0.81.
[0298] Example 14b
[0299] The method is carried out in accordance with Example 1, except that the first carbon-based particles are conventional graphite and the second carbon-based particles are conventional graphite.
[0300] Comparative Example 1
[0301] The same procedure is carried out as in Example 1, except that the first carbon-based particles, the second carbon-based particles, the silicon-carbon material and the silicon-oxygen material are mixed together and coated in a single layer.
[0302] Comparative Example 2
[0303] Refer to Example 1, except that T0 is 20.7 mm, T is 25 mm, K0 = (20.7 / 25) × 100% = 82.8%, T 100 24mm, K 100 =(24 / 25)×100%=96%; H 100 is 98μm, H is 90μm, R 100 =((98 / 90)-1)×100%=8.9%, H0 is 90.7μm, R0=((90.7 / 90)-1)×100%=0.78%.
[0304] Comparative Example 3
[0305] Refer to Example 1, except that T0 is 24.2 mm, T is 25 mm, K0 = (24.2 / 25) × 100% = 96.8%, T 100 24.8mm, K 100 =(24.8 / 25)×100%=99.2%; H 100 is 129.4μm, H is 90μm, R 100 =((129.4 / 90)-1)×100%=43.8%, H0 is 95.6μm, R0=((95.6 / 90)-1)×100%=6.22%.
[0306] Test Case
[0307] The lithium ion secondary batteries obtained in the examples and comparative examples were tested as follows:
[0308] 1. Normal temperature cycle test
[0309] At 25°C, in the charge and discharge window of 4.2V to 2.5V, 1C / 1C charge and discharge cycle was performed. The test process was as follows: first, 1C constant current charging to 4.2V, then constant voltage charging, cut-off current 0.05C, and finally 1C constant current discharge to 2.5V, and the test was repeated in this way. The number of times when the ratio of discharge capacity to the first discharge capacity (capacity retention rate) reached 80% was recorded in Table 2.
[0310] The ratio of the thickness of the battery at 50% SOC at the end of the cycle to the thickness in the initial state is recorded, which is the cycle expansion rate of the battery cell.
[0311] The ratio of the DCR value of the battery at 50% SOC at the end of the cycle to the DCR value in the initial state is recorded, which is the DCR growth rate.
[0312] 2. Fast charging window test
[0313] At room temperature, charge the battery cell nC (n=1, 2, 3, 4, 5) to 4.2V and then charge at a constant voltage with a cut-off current of 0.05C and let stand for 30min; discharge at 1C to 2.5V and let stand for 30min; repeat the charge and discharge cycle 20 times, and finally end the test after the battery cell is fully charged (100% SOC) and dissect it to observe whether lithium deposition occurs on the negative electrode side.
[0314] Record the maximum rate at which the battery does not release lithium, which is the fast charging window of the battery.
[0315] During the cyclic charge and discharge process, the temperature change of the battery during the charging process is recorded, and the maximum value is the maximum temperature rise of the battery.
[0316] The obtained results are recorded in Table 1.
[0317] Table 1
[0318]
[0319]
[0320] It can be seen from Table 1 that the battery of the present invention has a longer number of cycles, a larger fast charging window and a lower maximum temperature rise compared with the comparative example, indicating that the fast charging performance and safety performance of the battery are improved by arranging silicon-oxygen material on the surface of the negative electrode sheet away from the current collector, arranging silicon-carbon material on the surface of the negative electrode sheet close to the current collector, and controlling the thickness expansion coefficient K0 of the lithium-ion secondary battery.
[0321] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A lithium ion secondary battery, characterized in that: It comprises a battery cell and a shell, wherein the battery cell is located in a receiving space formed by the shell, and the battery cell comprises a positive electrode sheet, a separator and a negative electrode sheet; The positive electrode sheet includes a nickel-cobalt-manganese ternary material; The negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on at least one side of the negative electrode current collector; the negative electrode active material layer comprises a first negative electrode active material layer and a second negative electrode active material layer stacked in the thickness direction of the negative electrode sheet, the first negative electrode active material layer is away from the negative electrode current collector, and the second negative electrode active material layer is close to the negative electrode current collector; the first negative electrode active material layer comprises a silicon-oxygen material; the second negative electrode active material layer comprises a silicon-carbon material; The thickness expansion coefficient K0 of the lithium ion secondary battery is 85%-93%; The thickness expansion coefficient K0 = (T0 / T) × 100%, Wherein, T is the dimension of the accommodation space in the thickness direction, in mm, and T0 is the thickness of the battery cell when the lithium-ion secondary battery is in a 0% SOC state, in mm.
2. The lithium ion secondary battery according to claim 1, wherein K0 is 89%-92%; And / or, the thickness expansion coefficient K of the lithium ion secondary battery 100 The thickness expansion coefficient K is 95%-99.9%. 100 =(T 100 / T)×100%,T 100 is the thickness of the battery cell when the lithium-ion secondary battery is in a 100% SOC state, in mm; preferably, K 100 It is 97%-99%.
3. The lithium ion secondary battery according to claim 1 or 2, wherein: The rebound rate R of the negative electrode sheet 100 The rebound rate R is 8%-45%. 100 =[(H 100 -H) / H]×100%, H is the thickness of the negative electrode sheet, in μm, H 100 is the thickness of the negative electrode sheet when the lithium-ion secondary battery is in a 100% SOC state, in μm; Preferably, R 100 It is 25%-40%.
4. The lithium ion secondary battery according to claim 1 or 2, wherein: The rebound rate R0 of the negative electrode sheet is 0.1%-7%, and the rebound rate R0=[(H0-H) / H]×100%, H is the thickness of the negative electrode sheet, in μm, and H0 is the thickness of the negative electrode sheet when the lithium-ion secondary battery is in a 0% SOC state, in μm; Preferably, R0 is 0.5%-5%.
5. The lithium ion secondary battery according to claim 1 or 2, wherein: The mass proportion of the silicon-oxygen material in the first negative electrode active material is ≤20%; more preferably 0.1%-10%; And / or, the mass proportion of the silicon-carbon material in the second negative electrode active material is ≤15%; more preferably 0.1%-8%.
6. The lithium ion secondary battery according to claim 1 or 2, wherein: The silicon-oxygen material includes the element Si and the element O, and in the silicon-oxygen material, the mass ratio of the element Si to the element O is m1; the silicon-carbon material includes the element Si, the element C and the element O, and in the silicon-carbon material, the mass ratio of the element Si to the element O is m2; m1 <m2; Preferably, m1 / m2 is 0.001-0.12; more preferably 0.0023-0.05; Preferably, m1 is 0.8-1.2; more preferably 0.9-1; Preferably, m2 is 7.5-500; more preferably 20-400; Preferably, in the silicon-carbon material, the mass ratio of element Si to element C is 0.6-1.5; more preferably 0.9-1.
1.
7. The lithium ion secondary battery according to claim 1 or 2, wherein: The average particle size of the silicon-oxygen material is D1, and D1 is 5 μm-15 μm; the average particle size of the silicon-carbon material is D2, and D2 is 6 μm-14 μm; Preferably, the silicon-oxygen material further comprises element Li and / or element Mg; Preferably, the sphericity of the silicon-carbon material is 0.5-1.
8. The lithium ion secondary battery according to claim 5, wherein: The first negative electrode active material further includes first carbon-based particles, and the second negative electrode active material further includes second carbon-based particles; the average particle size of the silicon-oxygen material is D1, the average particle size of the silicon-carbon material is D2, the average particle size of the first carbon-based particles is D3, and the average particle size of the second carbon-based particles is D4; Meet: D3 / D1 is 1.1-2.3, D4 / D2 is 1.3-2.6; Preferably, D3 / D1 is 1.5-2, and D4 / D2 is 1.6-2.
2.
9. The lithium ion secondary battery according to claim 5, wherein: The first negative electrode active material further includes first carbon-based particles, and the second negative electrode active material further includes second carbon-based particles; the first carbon-based particles and the second carbon-based particles each independently include graphite; Preferably, the graphite satisfies at least one of the following characteristics: (1) The average particle size is 10 μm-20 μm; (2) having a coating layer, wherein the thickness of the coating layer is 100 nm to 200 nm; (3) interlayer spacing d002 is 0.3nm-0.36nm; (4) La is Lc is La is the average width of the graphite crystal along the a-axis, in Lc is the thickness of graphite crystal stacked along the c-axis direction, in units of (5) ID / IG is 0.86-1.2, ID is the intensity of the D peak in the Raman spectrum, where the D peak is located at 1300 cm -1 -1400cm -1 IG is the intensity of the G peak in the Raman spectrum, where the G peak is located at 1500 cm -1 -1650cm -1 .
10. The lithium ion secondary battery according to claim 1 or 2, wherein: When the lithium-ion secondary battery is in a 0% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d1, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d2; d1 is 0μm-35μm, and d2 is 0μm-26μm; preferably, d1 is 0μm-30μm, and d2 is 0μm-20μm; And / or, when the lithium-ion secondary battery is in a 100% SOC state, the vertical distance from the surface of the silicon-oxygen material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d3, and the vertical distance from the surface of the silicon-carbon material to the contact surface of the first negative electrode active material layer and the second negative electrode active material layer is d4; d3 is 0μm-40μm, and d4 is 0μm-35μm; preferably, d3 is 0μm-36μm, and d4 is 0μm-30μm.
11. The lithium ion secondary battery according to claim 1 or 2, wherein: The surface density of the first negative electrode active material layer is 1 mg / cm 2 -10mg / cm 2 , the porosity of the first negative electrode active material layer is 30%-45%; And / or, the surface density of the second negative electrode active material layer is 0.5 mg / cm 2 -6mg / cm 2 , the porosity of the second negative electrode active material layer is 25%-40%.
12. The lithium ion secondary battery according to claim 1 or 2, wherein: The negative electrode current collector comprises a metal layer and a conductive layer located on both sides of the metal layer, and the thickness of the conductive layer is 0.5 μm-2 μm; And / or, the first negative electrode active material layer further includes a first binder, and the second negative electrode active material layer further includes a second binder; preferably, the first binder and the second binder both include styrene-butadiene rubber.
13. The lithium ion secondary battery according to claim 1 or 2, wherein: The nickel-cobalt-manganese ternary material includes a substance with the chemical formula Li a Ni x Co y Mn z A k O2, where 0.9 ≤ a ≤ 1.2, 0.8 ≤ x ≤ 0.95, 0 < y ≤ 0.2, 0 < z ≤ 0.2, 0 ≤ k ≤ 0.05, and A is selected from at least one of Al, Zr, B, Y, Sr, W, Mg, Fe, Ti, and Nb; Preferably, the nickel-cobalt-manganese ternary material comprises single crystal particles, and the single crystal particles contain element B; More preferably, the mass content of element B in the single crystal particles is 200 ppm-1000 ppm.
14. The lithium ion secondary battery according to claim 1 or 2, wherein: The ratio of the surface density of the positive electrode sheet to the surface density of the negative electrode sheet is 1.5-2.5, preferably 1.7-2.
3.
15. The lithium ion secondary battery according to claim 1 or 2, wherein: The lithium-ion secondary battery further includes an electrolyte, and the electrolyte is located in the accommodation space; Preferably, the electrolyte comprises fluoroethylene carbonate; More preferably, the mass content of fluoroethylene carbonate in the electrolyte is 3%-25%.
16. The lithium ion secondary battery according to claim 1 or 2, wherein: The positive electrode sheet and the negative electrode sheet are stacked; the positive electrode sheet comprises: Positive electrode current collector; A plurality of positive electrode tabs extending from one side edge of the positive electrode current collector; a positive electrode active material layer located on at least one side of the positive electrode current collector; and A ceramic layer located on the edge surface of the positive electrode current collector on the positive electrode ear side; The ceramic layer is in contact with the positive electrode active material layer.